The Relationship Between Neuroprotective Activity and Antigenotoxic and Acetylcholinesterase Inhibitory Effects of Glaucium corniculatum Extracts - Fatma Gonca Kocanci; Buket Hamamcioglu; Belma Aslim (Universidade de São Paulo, 2022)
Abstract The purpose of this study was to investigate the relationship between the acetylcholinesterase (AChE) inhibitory and antigenotoxic effect with the neuroprotective activity of Glaucium corniculatum methanol and water extracts rich in rutin and quercetin flavonoids. Neuroprotective activity in terms of cell survival and development against oxidative damage was measured by MTT assay and microscopic analysis in H2O2-induced NGF-differentiated PC12 (dPC12) cells. QRT-PCR and western blot hybridization method was employed for the determination of AChE inhibition of the extracts in the same cell model, and the genotoxic and antigenotoxic effects were identified with Comet assay with human lymphocytes. H2O2-induced vitality loss in dPC12 cells was inhibited in pre-treated cells with these plant extracts. Moreover, extracts stimulated neurite formation and prevented the oxidative stress-induced reduction in neurite growth. In general, it was determined that G. corniculatum methanol extract containing higher amounts of rutin and quercetin was more effective than water extract in terms of AChE inhibitory, antigenotoxic and also neuroprotective effect. In this study, it was shown for the first time that both AChE inhibitory and antigenotoxic effects of G. corniculatum may be effective in neuroprotection and it's protective and therapeutic effects against neurodegeneration may be related to the flavonoid content.